1997
DOI: 10.1097/00007632-199712150-00009
|View full text |Cite
|
Sign up to set email alerts
|

Frozen Storage Affects the Compressive Creep Behavior of the Porcine Intervertebral Disc

Abstract: In vitro tests of frozen porcine intervertebral discs do not represent fresh behavior. Frozen storage appears to permanently alter disc behavior. The precise nature of any freezing-induced damage, and whether frozen storage similarly affects human discs, remains to be seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
3
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 67 publications
0
49
3
1
Order By: Relevance
“…In contrast, two recent reports showed that freezing at Ϫ20°C without DSMO decreased the compression stiffness of bovine humeral head cartilage and affected the compressive creep behavior of porcine intervertebral disc. 25,26 For the latter study, structural changes were indirectly demonstrated by measuring the swelling pressure and nuclear hydration (higher apparent permeability and lower swelling pressure for the frozen samples). 26 Logically, structural changes cause changes in tissue mechanical properties.…”
Section: Effect Of Cryopreservation On Mechanical Properties Of Cartimentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, two recent reports showed that freezing at Ϫ20°C without DSMO decreased the compression stiffness of bovine humeral head cartilage and affected the compressive creep behavior of porcine intervertebral disc. 25,26 For the latter study, structural changes were indirectly demonstrated by measuring the swelling pressure and nuclear hydration (higher apparent permeability and lower swelling pressure for the frozen samples). 26 Logically, structural changes cause changes in tissue mechanical properties.…”
Section: Effect Of Cryopreservation On Mechanical Properties Of Cartimentioning
confidence: 99%
“…25,26 For the latter study, structural changes were indirectly demonstrated by measuring the swelling pressure and nuclear hydration (higher apparent permeability and lower swelling pressure for the frozen samples). 26 Logically, structural changes cause changes in tissue mechanical properties. In searching for an explanation of the decreased mechanical properties of the cryopreserved cartilaginous tissues reported in this article, a cryosubstitution method was used during histological processing of the specimens.…”
Section: Effect Of Cryopreservation On Mechanical Properties Of Cartimentioning
confidence: 99%
“…[14][15][16][17][18] Compressive stress tests on knee cartilage showed comparable decreases in stiffness for both slow frozen ( −20…”
Section: Introductionmentioning
confidence: 99%
“…We chose to perform this experiment using bovine coccygeal motion segments for their easy availability and because this o ered the possibility to test the material without it having been frozen, since freezing has been shown to a ect creep properties of the intervertebral disc [19]. The main di erences with human lumbar segments are the lower cross-sectional area, higher apparent bone density, and the endplate convexity toward the disc.…”
Section: Discussionmentioning
confidence: 99%